Membrane lipid profile of in vitro-produced embryos is affected by vitrification but not by long-term dietary supplementation of polyunsaturated fatty acids for oocyte donor beef heifers - Leão, Beatriz C. S. [UNESP]; Rocha-Frigoni, Nathália A. S. [UNESP]; Nogueira, Ériklis; Cabral, Elaine C.; Ferreira, Christina R.; Eberlin, Marcos N.; Accorsi, Mônica F. [UNESP]; Neves, Thiago V. [UNESP]; Mingoti, Gisele Z. [UNESP] (CSIRO Publishing, 2017)
Dietary rumen-protected polyunsaturated fatty acids (PUFAs) rich in linoleic acid (LA) may affect embryo yield, and LA can modulate the molecular mechanisms of lipid uptake in bovine blastocysts produced in vitro. In embryos, membrane lipids, such as phosphatidylcholines (PCs) and sphingomyelins (SMs), affect cryopreservation success. The aim of the present study was to evaluate embryonic developmental rates after the IVF of oocytes retrieved from Nellore heifers fed for approximately 90 days with rumen-protected PUFAs rich in LA. In addition, we evaluated embryo cryotolerance and the membrane structure lipid composition using matrix-assisted laser desorption ionisation mass spectrometry of fresh and vitrified embryos. Embryo development to the blastocyst stage (mean 43.2%) and embryo survival after vitrification and warming (mean 79.3%) were unaffected by diet. The relative abundance of one lipid species (PC ether (PCe; 38:2, which means that this lipid has 38 carbon atoms and 2 double bonds in the fatty acyl residues) was increased after PUFAs supplementation. However, 10 ions were affected by cryopreservation; ions consistent with PC 32:0, PC 34:1, SM 24:1, PC 40:6 or PC 42:9, PC plasmalogen (PCp) 44:10 or PC 42:7, triacylglycerol (TAG) 54:9 and a not assigned ion (m/z 833.2) were lower in blastocysts that survived to the cryopreservation process compared with fresh blastocysts, whereas the abundance of the ions PC 36:3 or PC 34:0, PCe 38:2 or PC 36:6 and PC 36:5 or PCe 38:1 were increased after cryopreservation. Thus, the results demonstrate that the mass spectrometry profiles of PC, SM and TAG species differ significantly in bovine blastocysts upon cryopreservation. Because the lipid ion abundances of fresh and vitrified-warmed embryos were distinct, they can be used as potential markers of post-cryopreservation embryonic survival.
Keywords: blastocyst; bovine; mass spectrometry; Nellore cattle